Career Mathways: evaluating a novel initiative aimed at enhancing students' attitudes towards and appreciation of mathematics. (13th December 2021) - O'Meara, Niamh; Fitzmaurice, Olivia; Johnson, Patrick
Abstract: The power and value of mathematics cannot be underestimated in today's society. Thus, it is pertinent that education systems worldwide help students to develop an appreciation of the subject. However, research has shown that students often lose interest in science, technology, engineering and mathematics subjects, particularly mathematics, as they cannot see the relevance of it in their lives. This, in turn, leads to the development of negative attitudes towards mathematics, which have been shown to have a knock-on effect on students' academic performance, their participation and engagement with and motivation for the subject. The purpose of this paper is to describe and evaluate the impact of an innovative programme, known as Career Mathways, designed to improve secondary school students' attitudes towards mathematics by highlighting the applicability and usefulness of the subject in a multitude of careers. Career Mathways was piloted in five Irish secondary schools in the 2018/2019 academic year. It involved professionals ( n  = 13) from a variety of industries sharing insights with students ( n  = 156) and teachers ( n  = 6) about how they use mathematics in their day-to-day working lives. Based on these insights, a suite of resources for use in the classroom was developed and implemented with students across the five schools. This paper reports on the impact that this pilot study had on students' attitudes towards mathematics. The results from pre- and post-student surveys and teacher interviews show that Career Mathways had a moderate but positive influence on students' appreciation of the usefulness of mathematics and this impact was more profound among lower-achieving students.